Stampede Story Map - Truong, Renna (Bulletin - Association of Canadian Map Libraries and Archives (ACMLA), 2025)
Stampede Story Map by Adrian Stimson Adrian Stimson, a member of the Siksika Nation, was invited by the Calgary Institute for the Humanities at the University of Calgary to create a story map that highlights lesser-known and sometimes controversial histories of the Calgary Stampede. The first Calgary Stampede was held in 1912, evolving from the Calgary Exhibition, which began in 1886.